Anatomi Kejahatan Korporasi di Indonesia Relevansi Studi Kejahatan Korporasi - sri suhartati astoto (Fakultas Hukum Universitas Islam Indonesia, 2000)
The corporation growth as one of multi national company networks can notbe avoided. Such as fialds of banks, export-import company, insurance, sailing and ect. The refletion of technology development in differnt fields, suchs as communication technology, informatics, create condusive condition for the development of corporation. According to the criminal law and criminology the portion of economic law cares is complicated as the deviation in economic law as particular criminal action. The action in production and services, in intensive view point can interfere with in government program in economy but in extensive view point it can interfere with national economic system as privotal point of